The Nūr-Sîn Archive: Private Entrepreneurship in Babylon (603-507 B.C.) - Shiff, Laurence Brian (1987)
Ph.D. Dissertation; Oriental Studies; DissAbstr. 48/03 (Sept. 1987) 723-A/724-A; Supervisor: Erle V. Leichty; 223 contracts and letters, four generations of the Nūr-Sîn family; central figure: Iddin-Marduk s. Iqīša. "All available evidence indicates that the family operated a profit-oriented enterprise that was independent of any control or management by the palace and the temples".